The Development of Direct Democracy Mechanisms in Poland - Bednarz, Hanna (2013)
This working paper analyzes the development of the direct democracy institutions in Poland using the critical junctures and path dependence methodology. These institutions have been present in the Polish constitutional law scholarship since the beginning of the 20th century. Their introduction into the law was nevertheless a difficult compromise between the political actors. Throughout the past century, direct democracy mechanisms were seldom used, partly due to the fact that the citizens were not allowed to make a final decision as to their application. As the study shows, the current legislation on direct democracy is still rooted in the Communist times and marked by the Legislature's and Executive's deep distrust in the people’s ability to make conscious decisions.